2010
DOI: 10.1037/a0020146
|View full text |Cite
|
Sign up to set email alerts
|

Coherence between emotional experience and physiology: Does body awareness training have an impact?

Abstract: Two fundamental issues in emotion theory and research concern: (a) the role of emotion in promoting response coherence across different emotion systems; and (b) the role of awareness of bodily sensations in the experience of emotion. The present study poses a question bridging the two domains; namely, whether training in Vipassana meditation or dance, both of which promote attention to certain kinds of bodily sensations, is associated with greater coherence between the subjective and physiological aspects of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
214
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(233 citation statements)
references
References 98 publications
17
214
0
2
Order By: Relevance
“…In a recent study, mindfulness meditators showed significantly more coherence between physiological changes and their subjective awareness of emotional responses than did either professional dancers (ballet and modern dance) or control subjects with no meditation or dance experience (Sze, Gyurak, Yuan, & Levenson, 2010). Mindfulness meditators were more aware of their visceral responses and thereby more aware of their emotions.…”
Section: Full and Accurate Awarenessmentioning
confidence: 99%
“…In a recent study, mindfulness meditators showed significantly more coherence between physiological changes and their subjective awareness of emotional responses than did either professional dancers (ballet and modern dance) or control subjects with no meditation or dance experience (Sze, Gyurak, Yuan, & Levenson, 2010). Mindfulness meditators were more aware of their visceral responses and thereby more aware of their emotions.…”
Section: Full and Accurate Awarenessmentioning
confidence: 99%
“…A robust finding in this context is that subjectively reported feelings are associated with particular changes in heart-rate, skin conductance and other physiological parameters (e.g., Lang et al, 1999). Interestingly, this association is often only moderate in general population (Mauss, Levenson, McCarter, Wilhelm, & Gross, 2005), but increased in expert dancers (Sze, Gyurak, Yuan, & Levenson, 2010). This suggests that expertise in the bodily expression of emotion can augment the extent to which arousal influences the subjective experience of feelings and there are reasons to believe that this could enhance sensitivity to the emotion expressed in the Running head: MOVEMENT EXPERTISE AND AFFECTIVE SENSITIVITY 5 movements of others.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that this is observed only in relation to familiar forward presentations of relevant movements lends support to the idea that relevant expertise rather than spurious stimulus characteristics are mediating these effects. In a final analysis we examined whether dance expertise may also modulate the extent to which subjective experiential and psychophysiological facets of emotional responsiveness are coupled, which is thought to provide another indicator of affective sensitivity (Sze, et al, 2010). Thus, as explained in the analysis section, the …”
Section: Correlations Between Subjective Affective Experience and Phymentioning
confidence: 99%
“…Although there exists strong theoretical support for the construct of emotional response coherence, empirical results have been inconclusive (Barrett 2006;Sze et al 2010). While some studies found support for coherence (e.g.…”
mentioning
confidence: 99%